Towards Financial Education Transformation: Accounting Computer Application Training for Teachers and Students of SMA Negeri 1 Dolok Batu Nanggar - Silalahi, Amlys Syahputra; Lubis, Andrew Satria; Lubis, Muhammad Arif; Astuti, Windi (Talenta Publisher, 2023)
This community engagement initiative took place within the premises of SMA Negeri 1 Dolok Batu Nanggar. Online Accounting Computer Applications serve as a valuable tool for simplifying financial report preparation. The objective of this community engagement was to improve participants' understanding of financial record keeping, presentation, and reporting, with the aim of enabling faster, more accurate financial reporting. The engagement activities involved socialization, simulations, and practical exercises, illustrating how to record various transactions in accordance with common industry standards using the Accounting Computer Application. Twenty-five participants, consisting of five teachers and twenty-five students from SMA Negeri 1 Dolok Batu Nanggar, were involved in the program. The post-test results revealed a significant increase in participants' knowledge and understanding of the Accurate Online application. Approximately 70% to 80% of the participants reported familiarity with the application and its benefits, a substantial improvement from the initial 30%. The training and mentoring provided during this initiative is expected to empower both teachers and students, enabling them to enhance their competence in financial report preparation for their future business ventures and in offering financial reporting services to companies.